Responses of fungi to tropane alkaloids produced by a medicinal plant Hyoscyamus muticus (Egyptian Henbane) - Abdel-Motaal, F. F; Nassar, M. S. M; El-Zayat, S. A; El-Sayed, M. A; Ito, S (Folia microbiologica, 2009)
Antifungal activity of hyoscyamine (Hcy) and scopolamine (Sco) were determined by TLC-bioautography against fungi associated with H. muticus grown in Egypt, and those isolated from other plants grown in Japan. All 40 fungal strains were tolerant to Sco and sensitive to Hcy, exhibiting a growth inhibition zone around the Hcy spot on the bioautography plate. The strains were grouped into three types based on the appearance of the inhibition zone: (i) 17 strains exhibiting a clear inhibition zone, which remained clear at 8 d after incubation (type I); (ii) 22 strains exhibiting the inhibition zone with a brown circle surrounding the zone and regrowth within the inhibition zone (type II); (iii) 1 strain exhibiting the inhibition zone with no brown circle and regrowth within the inhibition zone (type III). In the type II and III strains, Hcy disappeared, and other alkaloids were found in the inhibition zones in its place. Hcy feeding experiments using Penicillium purpurogenum (type II) and Cunninghamella elegans (type III) revealed that these fungi may convert Hcy to a new alkaloid compound.
Keywords: financování organizované; Financing, Organized; léčivé rostliny; Scopolamine; Antifungal Agents; Microbial Sensitivity Tests; Plants, Medicinal; mikrobiální testy citlivosti; atropin; Cunninghamella; antifungální látky; skopolamin; Atropine; Hyoscyamus; Penicillium